2018
DOI: 10.1371/journal.pone.0196951
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium

Abstract: BackgroundOdd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established.ObjectiveTo elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The possible reasons for the presence of circulating C23:0 in rat brain was found to be either the exogenous intake through milk or endogenous production by the elongation of odd carbon chain fatty acid C17:0 37,38 . Recently, a genome-wide association meta-analysis of circulating odd carbon chain fatty acids revealed that C23:0 is predominantly a component of sphingolipids and is associated with a common variation in ceramide synthase CERS4 gene 39 . However, there is no report underlining the role of odd carbon chain SPLs in cancer patients till date.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons for the presence of circulating C23:0 in rat brain was found to be either the exogenous intake through milk or endogenous production by the elongation of odd carbon chain fatty acid C17:0 37,38 . Recently, a genome-wide association meta-analysis of circulating odd carbon chain fatty acids revealed that C23:0 is predominantly a component of sphingolipids and is associated with a common variation in ceramide synthase CERS4 gene 39 . However, there is no report underlining the role of odd carbon chain SPLs in cancer patients till date.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, fatty acid composition in tissues or the circulation are increasingly being utilised as biomarkers of dietary fat [ 12 ]. Two odd-chain saturated fatty acids, pentadecanoic acid (15:0) and heptadecanoic acid (17:0), and one trans -fatty acid, trans -palmitoleic acid ( t 16:1n-7), are increasingly used as biomarkers of dairy fat intake because they are mainly found in ruminant foods such as milk and are not strongly influenced by genetic variation [ 12 , 13 ]. Thus, their levels correlate with dairy fat consumption assessed through weighed diet records and 24-hour dietary recalls and change in accordance with dairy food intake in randomised controlled trials [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The median sample size per analysis was 7,811 (min=284; max=17,267), including analyses of 10 monounsaturated fatty acids (MUFAs), 15 saturated fatty acids, 6 omega 3 PUFAs, 11 omega six PUFAs and 11 other characteristics (Supplementary table 1). The 15 GWAS analyses corresponded to seven independent studies or consortia and 15 separate publications [35][36][37][38][39][43][44][45][46][47][48][49][50][51][52] . An interaction study was the only fatty acid GWAS excluded 53 .…”
Section: Fatty Acid Datasetsmentioning
confidence: 99%
“…The vast majority of the GWAS analyses were conducted in European ancestry populations (11/15), two were conducted in populations of East Asian ancestry, one in a population of South Asian ancestry and one in a trans-ethnic GWAS of Europeans and East Asians. We collated full summary data from 13 of 15 publications, corresponding to six independent consortia or cohort studies: CHARGE 34,[43][44][45]48,49,51,52 , SCHS 35 , the Framingham study (FHS) 37 , the TwinsUK/KORA study 39 , the NHAPC/MESA-CHI study 36,48 and Kettunen et al 38 .…”
Section: Fatty Acid Datasetsmentioning
confidence: 99%